Image Registration Techniques: A Review (International Journal of Engineering and Computer Science, 2015)
- Image Registration is process of aligning two different images of same scene taken at a different time, from differentview point, or may be different capturing device. There are various methods have been proposed for image registration processing inlast some years. But they are not commonly used in practice because of several drawbacks. The goal of the paper is to review andunderstand image registration process and its different methods.